Self‐assembled free‐floating nanomaterials from sequence‐defined polymers. Issue 21 (11th July 2021) - Babi, Jon; Zhu, Linglan; Lin, Angela; Uva, Azalea; El‐Haddad, Hana; Peloewetse, Atang; Tran, Helen
Abstract: Sequence‐defined polymers can be programmed to self‐assemble into precise nanostructures for applications in biosensing, drug delivery, optics, and molecular computation. Inspired by the natural self‐assembly processes present in biological protein and DNA systems, sets of molecular design rules have emerged across materials classes as instructions to build a variety of tunable structures. This review highlights recent advances in self‐assembled sequence‐defined and sequence‐specific polymers across peptides, peptoids, DNA, and non‐biological synthetic materials, with a focus on synthesis, assembly processes and overall structure. Specifically, these self‐assembled structures are free‐floating, as such constructs can potentially serve as a platform for the aforementioned applications. Emphasis is placed on the molecular design of polymers that self‐assemble into zero‐dimensional, one‐dimensional, two‐dimensional, or three‐dimensional nanostructures. With the development of automated syntheses and increasing control over self‐assembly, future work may focus on emerging classes of compatible hybrid materials with exciting directions toward new architectures and applications. Abstract :